PENGARUH LITERASI DIGITAL TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SMP DI SMPN 2 PONDOK SALAM - Dewi Dahlianti; Ligar Meilasari; Ipah Latipah; Eka Puspitasari; Muhamad Wirahadikusumah; Dinny Mardiana (STKIP Pesisir Selatan, 2026)
One of the challenges of 21st-century learning is the low level of students’ critical thinking skills in analyzing and evaluating digital information, highlighting the importance of digital literacy. This study aims to analyze students’ critical thinking skills, examine their level of digital literacy, and determine the effect of digital literacy on the critical thinking skills of junior high school students. The research employed a quantitative approach with a survey method involving 60 students of SMP Negeri 2 Pondoksalam, Purwakarta Regency, selected through purposive sampling. Data were collected using Likert-scale questionnaires and analyzed through descriptive and inferential statistics, including validity, reliability, normality, t-test, F-test, and coefficient of determination (R²). The findings revealed that students’ critical thinking skills were categorized as good, while their digital literacy was also categorized as good. Hypothesis testing showed that digital literacy had a positive and significant effect on students’ critical thinking skills with a significance value of 0.000 < 0.05 and a coefficient of determination (R²) of 0.372, indicating that 37.2% of students’ critical thinking skills were influenced by digital literacy. The novelty of this study lies in strengthening the role of digital literacy as a supporting factor in improving students’ critical thinking skills through the analytical, selective, and responsible use of digital technology and information.